(untitled) (Scientific journal of the Fergana State University, 2023)
The article investigates the polarization characteristics of radiation diffusely reflected when illuminating a semi-infinite light-scattering medium with unpolarized radiation. The formation of neutral points of polarization of Babinet, Brewster and Arago in the angular polarization characteristics of the secondary radiation is shown. Comparisons are made between the results of exact numerical calculations with approximate analytical formulas, and the physical conditions for the appearance of neutral points are analyzed depending on the angles of illumination and the scattering factor.